PENERAPAN PENDIDIKAN KARAKTER RELIGIUS PADA SISWA SMA AL-RIFA’IE SATU GONDANGLEGI MALANG - Vina Viviana; Rosichin Mansur; Moh Muslim (VICRATINA, 2022)
In modern times, there are so many cases of moral degradation that should not have occurred. One of them is the crisis in the world of moral education. As well as students who often say dirty, lack of manners towards their elders, often fight and so on. This is due to the lack of character cultivation in students, let alone religious character education. The cultivation of religious character values can start from the family environment, school, and society, to make students' morals even better. So researchers are interested in researching this. This research using this type of research is a case study using a qualitative approach. The data collection procedure is carried out using observation, interviews and documentation. The conclusions of this study include: (1) There is a religious character planning for Al-Rifa'ie Satu High School students by making RPP, Satpel, holding meetings every month and evaluating students. (2) The implementation of the application of religious character education to students of Al-Rifa'ie Satu High School using habituation methods, suri tauladan methods, advice methods, and methods of recommendation or prohibition, (3) The results of the implementation of religious character education to students at Al-Rifa'ie Satu High School are very impactful for students, namely from a spiritual and social point of view.